STUDENTS’ PERCEPTIONS ON THE IMPLEMENTATION OF PHONOLOGY, MORPHOLOGY, SYNTAX AND SEMANTICS ON STUDENTS’ ENTREPRENEURSHIP AT ENGLISH DEPARTMENT UNIVERSITAS BANDAR LAMPUNG - yanuarius yanu dharmawan; Nabila Rosa Trinanda; Gabrielle Ghaniiyyu Nafinoor (BEYOND LINGUISTIKA (Journal of Linguistics and Language Education), 2021)
The aim of this research is to investigate students' perceptions on the implementation of a branch of linguistics courses that function for student entrepreneurship. Entrepreneurship is described as the ability and actions of a person to deal with life's challenges to obtain opportunities while balancing the various risks that may be encountered. Therefore, we emphasize the need to develop entrepreneurial potential in students so that, after graduation, they can successfully adapt to changing job market conditions and as a result, realize their professional career plans to be successful. The instruments used in this study were questionnaires and interviews. This research was conducted on students in the fifth and seventh semester of the 2020/2021 academic year of the English Department at Universitas Bandar Lampung. The results showed that students had positive perceptions of entrepreneurship. The benefits they feel by applying phonology, morphology, syntax, and semantics make them motivated and this is considered quite effective for them to be entrepreneurial. Besides, they claim that they are more confident in mastering the branch of linguistics.